2009
DOI: 10.1002/jor.20914
|View full text |Cite
|
Sign up to set email alerts
|

Low dose metal particles can induce monocyte/macrophage survival

Abstract: Aseptic loosening results in pain, loss of function, and ultimately prosthetic joint failure and revision surgery. The generation of wear particles from the prosthesis is a major factor in local osteolysis. We investigated the effects of such wear particles on the survival of monocytes and macrophages, populations implicated in wear particle-driven pathology. Particles from titanium aluminum vanadium (TiAlV) and cobalt chromium (CoCr) alloys were generated in-house and were equivalent in size (0.5-3 mm) to tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Although this concept is well known in orthopedic related literature, absence of evidence, however, was present in the dental implant related literature. In fact, wear particles can promote monocyte/macrophage survival in vitro possibly via an endogenous mediator (Lacey et al 2011). Literature analysis suggests that titanium particle-induced acute inflammation is due to activation of the NALP3 inflammasome, which leads to increased IL-1b secretion and IL-1-associated signaling, including neutrophil recruitment .…”
Section: Discussionmentioning
confidence: 99%
“…Although this concept is well known in orthopedic related literature, absence of evidence, however, was present in the dental implant related literature. In fact, wear particles can promote monocyte/macrophage survival in vitro possibly via an endogenous mediator (Lacey et al 2011). Literature analysis suggests that titanium particle-induced acute inflammation is due to activation of the NALP3 inflammasome, which leads to increased IL-1b secretion and IL-1-associated signaling, including neutrophil recruitment .…”
Section: Discussionmentioning
confidence: 99%
“…This theory is supported by evidence showing that both soluble and particulate debris derived from CoCrMo can induce monocyte–macrophage activation and the secretion of numerous proinflammatory cytokines [28]. Even low doses of CoCrMo promote macrophage survival ( in vitro ), which could contribute to the increased numbers of macrophages in the regions of joint implant failure and the local inflammatory reaction and osteolysis [29].…”
Section: Host Response To Biomaterials and Infectionmentioning
confidence: 97%
“…It has been shown that metal ions such as vanadium and cobalt chromium decrease monocyte and macrophage survival in a dose-dependent manner [4]. …”
Section: Introductionmentioning
confidence: 99%